2010
DOI: 10.1007/s00384-010-1018-2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous vs. staged resection for synchronous colorectal liver metastases: a metaanalysis

Abstract: Simultaneous resection is safe and efficient in the treatment of patients with SCLM while avoiding a second major operation. In appropriately selected patients, simultaneous resection might be considered as the preferred treatment. Since heterogeneity was detected, caution is needed in interpretation of the results. Better designed, adequately powered studies are required for addressing this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 34 publications
3
81
1
4
Order By: Relevance
“…This has been shown consistently in the literature 7,9,12,20,22,[24][25][26] and in our study. Even in studies where morbidity was significantly higher in Simultaneous resection n = 100 CRC cases with liver resection and the simultaneous group, the overall length of stay in this group was still shorter.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This has been shown consistently in the literature 7,9,12,20,22,[24][25][26] and in our study. Even in studies where morbidity was significantly higher in Simultaneous resection n = 100 CRC cases with liver resection and the simultaneous group, the overall length of stay in this group was still shorter.…”
Section: Discussionsupporting
confidence: 93%
“…5,6,8,12,20,21,25,26,28 In these series, 5year OS for simultaneous resections ranged from 29% to 55%; our results suggest that com parable outcomes are achieved in routine practice. We report outcomes of patients who underwent staged resections for illustrative purposes only.…”
Section: Discussionmentioning
confidence: 52%
“…Chen et al [27] performed a meta-analysis on 14 studies that retrospectively compared concomitant resection to staged resection in patients with resectable synchronous hepatic metastases. The analysis was performed on a total of 2204 patients of whom 1384 (ages 56-64.9 yrs) had received simultaneous resection and 817 (ages 58-61 yrs) staged resection.…”
Section: Timing Of Surgical Resection Of Primary Tumour and Synchronomentioning
confidence: 99%
“…The level of evidence for OS and postoperative morbidity in case of simultaneous vs. staged resection of the primary tumour and hepatic metastases was downgraded to moderate (Table 10). It is therefore plausible that there is no difference in OS after simultaneous resection compared to staged resection of the primary tumour and resectable synchronous liver metastases [27] but that concomitant resection of the primary tumour and synchronous liver metastases results in lower postoperative morbidity compared to staged resection [3,27].…”
Section: Conclusion Based On Grade Profilesmentioning
confidence: 99%
“…Because simultaneous major hepatectomy was associated with severe morbidity rate (36.1% vs. 17.6%) and mortality (8.3% vs. 1.4%) [13], a staged operation for synchronous and multiple hepatic nodules has been recommended with a delay of at least 3 months after the primary resection. In contrast, based on the results of simultaneous resection to have similar operative times, intraoperative blood loss, and complications [11], recent studies showed simultaneous resection to enhance safety [3,14,15]. According to the safety concepts for such surgical procedures, simultaneous colorectal and liver resections have been evaluated as grade C under the recommended guidelines [16], however, no randomized trials have been published.…”
Section: The Role Of Surgical Proceduresmentioning
confidence: 99%